Context-Specific Affective and Cognitive Responses to Humanoid Robots - Yoonhyuk Jung; Eunae Cho (International Telecommunications Society (ITS), 2018)
The uncanny valley model explains the relationship between the resemblance that robots have to humans and attitudes towards these humanoid robots. This model is an influential theory in human-robot interaction and helps us understand individuals' attitudes towards humanoids. Despite its extraordinary worth, prior research has examined the model in general or contextfree situations. Given that humanoids have begun to permeate social spheres and are used in actual business areas, it is important to investigate the uncanny valley in specific and actual situations. Additionally, there has been little work on the impact of affective responses presented in the uncanny valley to other appraisals of humanoids. To remedy these constraints, this study tries to explore context-specific affective and cognitive responses to humanoids in the framework of the uncanny valley. In particular, this study examines the effect of affective responses on trust, which is regarded as a critical cognitive factor influencing technology adoption, in two situations: hotel reception (low expertise) and tutoring (high expertise). By providing a richer understanding of human reactions to humanoids, this study expands on the uncanny valley theory and ultimately makes contributions to research on human-robot interactions.
Keywords: 330; human-robot interaction; uncanny valley; trust; context